Stress Management Application on Expressed Emotions of Families with Schizophrenia in Online Family Psychoeducation: Case Report - Diorarta, Raphita; Susanti, Herni; Wardani, Ice Yulia (Jurnal Keperawatan Profesional (KEPO), 2025)
The family is the individual who is closest to the patient so that it is considered to have the most influence on the life of the sufferer. Stress management is one of the sessions in family psychoeducation (FPE). In the Covid-19 pandemic situation which has a very rapid spread of the virus, online care remains a powerful solution and is potentially needed so that online family psychoeducation is the right choice in this situation. The purpose of providing this therapy was to determine to the effectiveness of stress management in FPE sessions in reducing Expressed Emotion (EE) in families with schizophrenia. The writing of this scientific paper was a case report. The intervention was carried out for 6 weeks with a frequency of once a week and an average duration of 45-60 minutes per session. The assessment used was a family questionnaire to assess the level of EE in the family. The final evaluation of the implementation of stress management in the online FPE session given showed a decrease in EE owned by the family. This case report recommends implementing stress management in FPE sessions to reduce EE which can also work well in online implementation.